2010
DOI: 10.1055/s-0030-1253351
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Real-Time PCR Methodology in the Neonatal Detection of Turner Syndrome

Abstract: Turner syndrome (TS) is the complete or partial loss of the second sex chromosome, occurring in 1:5 000 girls. Early recognition allows appropriate therapy for short stature and puberty. Neonatal diagnosis of TS permits detection of associated malformations, minimizing sequels. Aiming to develop a molecular method for the diagnosis of TS we employed blood samples stored on filter paper. We evaluated 78 female controls, 25 TS girls with 45,X karyotype, and 32 TS patients with other karyotypes. After DNA extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…We previously studied the real-time PCR technique in the identification of TS (Rocha et al, 2010) by quantifying the ARSE/GAPDH genes ratio. In our previous study, we obtained 100% sensitivity and specificity for TS patients and the 45,X karyotype, but only 56% sensitivity in patients with mosaicism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously studied the real-time PCR technique in the identification of TS (Rocha et al, 2010) by quantifying the ARSE/GAPDH genes ratio. In our previous study, we obtained 100% sensitivity and specificity for TS patients and the 45,X karyotype, but only 56% sensitivity in patients with mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…PCRs were carried out in a 7500 Real-Time PCR System (Applied Biosystems), and the parameter setting was conducted with the aid of the SDS-Sequence Detection System version 1.2, 7500 Systems SDS Software (Applied Biosystems). The thermocycling conditions used were 50°C for 2 min; 95°C for 10 min; 40 cycles at 95°C for 15 s; and 60°C for 1 min; fluorescence readings were recorded during the final step of each cycle (Rocha et al, 2010).…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt et al (2000) reported a method for the prenatal diagnosis of somatic aneuploidies and SCAs based on the gene copy number. Other reports include the analysis by quantitative polymerase chain reaction (qPCR) of different genes for the diagnosis of TS, such as the androgen receptor (AR) gene (Rocha et al, 2010), dose-sensitive sex reversal-adrenal hypoplasia congenital critical region on the X chromosome gene 1 (DAX1), and the arylsulfatase E gene (ARSE) (Rocha et al, 2005), and for the diagnosis of KS, such as the AR and short stature homeobox (SHOX) genes (Ottesen et al, 2007;Aksglaede et al, 2012). We have previously published, in already diagnosed patients, that the identification of TS could be done by means of quantifying copy number of SHOX and VAMP7 (vesicle-associated membrane protein 7) pseudoautosomal genes together with the SRY (Ibarra-Ramirez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The dosage reduction of genes located in PARs1 and 2, which is inherent to the complete or partial loss of the second sex chromosome, can be sensitively quantified by quantitative polymerase chain reaction (qPCR), as reported for the ARSE gene in Xp22.33 (Rocha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%